Long-term occurrence of Trichuris species in wild ruminants in the Czech Republic - Nechybová, Stanislava; Vejl, Pavel; Hart, Vlastimil; Melounová, Martina; Čílová, Daniela; Vašek, Jakub; Jankovská, Ivana; Vadlejch, Jaroslav; Langrová, Iva (Parasitology research, 2018)
The aim of this study was to identify Trichuris species in wild ruminants from 32 localities in the Czech Republic using morphological and molecular methods (ITS1-5.8S RNA-ITS2 region polymorphisms). Trichurids were obtained from 176 wild ruminants (roe deer, sika deer, red deer, fallow deer and mouflons) that were culled between 2009 and 2017. Trichuris discolor is the predominant trichurid of all of the above-mentioned wild ruminants, whereas Trichuris ovis was identified less frequently in roe deer, fallow deer, sika deer and mouflons. Red deer were parasitised exclusively by T. discolor. Young hosts under 1 year of age were more intensively infected by trichurids than were adults (χ2 = 32.02, p = 0.00). Trichurid prevalence results obtained through coprological methods and those based on parasitological dissections differed significantly (χ2 = 16.26, p = 0.00). The regression analysis indicated that the eggs per gram (EPG) threshold (20 EPG) was exceeded only if the host was parasitised by more than 7 trichurid females. Full concordance between the positive results obtained by the coprological methods and those obtained via direct dissections was achieved when the number of trichurid females per host exceeded 51.
Keywords: Prevalence; Animals, Wild; Trichuris; trichurióza; Česká republika; ITS1-5.8S rRNA-ITS2 region; mužské pohlaví; Sheep, Domestic; vysoká zvěř; Czech Republic; ovce domácí; Effectiveness of coprology; divoká zvířata; ženské pohlaví; zvířata; Game ruminants; Deer; Trichuriasis; Female; Trichuris discolor; Trichuris ovis; Male; Animals